Kajian Aspek Fisiologik Beauveria bassiana dan Virulensinya terhadap Helicoverpa armigera - Suharto Suharto; Endang Budi Trisusilowati; Hari Purnomo (Jurnal Perlindungan Tanaman Indonesia, 1998)
Study on physiological aspects of six isolates of Beauveria bassiana and their virulence to Helicoverpa armigera was conducted in laboratory. Six isolates were obtained from different host and geographical locations. Stocks cultures was freeze dried and when required they were reconstituted and placed onto fresh SDA and incubated for seven days. The result of research indicated that color of all colony are white. Colony growth rate was affected by kind of the media. The highest colony growth was found from rice bug Jember isolate (JeLa). The hyphal growth rate per days was significantly different between isolates. The highest hyphal growth rate was found from coffee berry borer Jember isolate (JeHh). The number of spore per ml in SDA was relatively higher than PDA. The number of spore was significantly different between isolates both in SDA and PDA. The highest number of spore was found from JeLa and JeHh in SDA and PDA, respectively. The germination of spore 24 hours after inoculation was found from JeLa and significantly different than other isolates, although the rate of germination per hour was not significantly different. The number of spore germination was increased by temperature change from 27oC to 45oC. However, the increase of temperature up to 50oC, the number of spore germination become lower than 27oC. Spore germination was decreased by irradiation of UV light. Among six isolates, the highest virulence to H. armigera was found from JeLa isolate.